Model Pembangunan Kawasan Perbatasan Kalimantan Utara Yang Berpihak Pada Masyarakat Hukum Adat - Basri Basri (JURNAL AKTA YUDISIA, 2020)
iAbstract               The North Kalimantan Border Area is largely inhabited by indigenous peoples. Development of Border Areas is a necessity, because the development of border areas is part of national development. Indigenous peoples in the border region have the character and local wisdom that determines with other communities, so that the development model in other regions does not necessarily show partiality to the indigenous peoples in the border region. There are two questions in this study; first, regarding the characteristics of the border problems of North Kalimantan Province and their implications for indigenous peoples,? and secondly; Does the development model in the border area favor indigenous peoples?               This type of research is normative juridical research, with qualitative analysis. The research objective to be achieved is to produce an appropriate development model applied in areas that connect to the copyright of indigenous peoples in the border region, and produce specific findings for. Reducing legal and policy barriers in finding development models in the border region in North Kalimantan that favor the indigenous peoples.Keywords; Models, development, indigenous peoples, borders